The Implementation of Digital-Based Public Services through the Akudicari Application: A Case Study on the Population and Civil Registration Office of Badung Regency from the Perspective of Good Governance - Yolanda, Agnes Yosi; Wirantari, I Dewa Ayu Putri (Universitas Padjadjaran, 2025)
This study analyzed the implementation of digital-based public service delivery through the Akudicari application at the Population and Civil Registration Office (Disdukcapil) in Badung Regency, Bali Province, Indonesia, within the framework of good governance principles. Akudicari, a digital platform for monitoring the status of civil documents, was developed in response to limited face-to-face services during the COVID-19 pandemic, aiming to promote efficiency, transparency, and accountability. This research employed a qualitative descriptive approach with data collection techniques including interviews, observations, and document analysis. The findings indicate that the Akudicari application reduced service time by 30%, broadened public access to online information, and minimized illicit practices such as service brokerage. The principles of good governance were reflected in transparency, accountability, effectiveness, responsiveness, and public participation. However, challenges persisted, such as low digital literacy in rural areas, limited internet infrastructure, and disparities in human resource capacity. Strategies implemented included regular staff training, system updates, and intensified public outreach. This study provides empirical insights into strengthening local digital public service governance and proposes the Akudicari application as a scalable, accountable, and adaptive model for digital transformation in government services.